Flesh matters: The body in cognition. (6th July 2018) - Shapiro, Lawrence A.
Abstract : Embodied cognition emphasizes the importance of the body to cognition, but what is the nature of this importance? For some advocates, the body provides a computational resource within the context of a larger cognitive system. For others, the body constrains cognition, such that differently embodied organisms will differ cognitively as well. I examine these distinct conceptions of embodiment, defending the greater interest of the second. I argue as well that judgments of the body's significance in cognition do not, as contestants on both sides of the debate often insist, depend on showing the body to be a constituent in cognition.